Septins: Active GTPases or just GTP‐binding proteins?. Issue 1 (30th August 2018) - Abbey, Megha; Gaestel, Matthias; Menon, Manoj B.
Abstract: Septins are conserved cytoskeletal proteins with unique filament forming capabilities and roles in cytokinesis and cell morphogenesis. Septins undergo hetero‐oligomerization and assemble into higher order structures including filaments, rings, and cages. Hetero‐ and homotypic interactions of septin isoforms involve alternating GTPase (G)‐domain interfaces and those mediated by N‐ and C‐terminal extensions. While most septins bind GTP, display weak GTP‐hydrolysis activity and incorporate guanine nucleotides in their interaction interfaces, studies using GTPase‐inactivating mutations have failed to conclusively establish a crucial role for GTPase activity in mediating septin functions. In this mini‐review, we will critically assess the role of GTP‐binding and ‐hydrolysis on septin assembly and function. The relevance of G‐domain activity will also be discussed in the context of human septin mutations as well as the development of specific small‐molecules targeting septin polymerization. As structural determinants of septin oligomer interfaces, G‐domains are attractive targets for ligand‐based inhibition of septin assembly. Whether such an intervention can predictably alter septin function is a major question for future research.